IMMU-09. HETEROGENEOUS INTRA-TUMORAL ANTIGEN EXPRESSION IN RELATION TO IMMUNOTHERAPY OF HIGH GRADE GLIOMA. (5th November 2018) - Barish, Michael; Weng, Lihong; D'Apuzzo, Massimo; Zhai, Yubo; Brito, Alfonso; Chang, Brenda; Sarkissian, Aniee; Starr, Renate; Chang, Wen-Chung; Aguilar, Brenda; Naranjo, Araceli; Blanchard, Suzette; et al.
Abstract: Glioblastoma (GBM) remains an almost universally fatal brain tumor despite numerous on-going efforts to devise novel and efficacious therapies. We are exploring one approach, immunotherapy with genetically modified T cells expressing chimeric antigen receptors (CARs) targeting specific tumor antigens. While adoptive CAR T cell immunotherapy has shown promising efficacy in pre-clinical and clinical studies, tumor relapses nevertheless occur, a reflection of our incomplete understanding of target antigen expression in GBM. We have previously suggested from analysis of inter-tumoral heterogeneity in primary tissues from patients with GBM that, in principle, a multiple antigen approach targeting IL13Rα2, HER2 and EGFR could effectively target approximately 93% of patient tumors. Our most recent observations, working with this same cohort of patient tumor samples, indicate that individual GBM lesions are composed of numerous subpopulations of tumor cells with differing target antigen expression patterns. This high degree of intra-tumoral heterogeneity, evident in the spatial extent ("granularity") of target antigen expression patterns and their relations to tumor architecture, may complicate single- and multiple-target immunotherapies by contributing to antigen escape and tumor recurrence.